Asylum speakers : Caribbean refugees and testimonial discourse - Shemak, April Ann (Fordham University Press, 2011)
Offering an interdisciplinary study of refugees in the Caribbean, Central America, and the United States, this book relates current theoretical debates about hospitality and cosmopolitanism to the actual conditions of refugees.